2018
DOI: 10.1101/469064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Target-specific co-transmission of acetylcholine and GABA from a subset of cortical VIP+ interneurons

Abstract: The modulation of cortex by acetylcholine (ACh) is typically thought to originate from long-range projections arising in the basal forebrain. However, a subset of VIP interneurons express ChAT, the synthetic enzyme for ACh, and are a potential local source of cortical ACh. Which neurotransmitters these VIP/ChAT interneurons (VCINs) release is unclear, and which post-synaptic cell types these transmitters target is not known. Using quantitative molecular analysis of VCIN pre-synaptic terminals, we show expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Our results correspond with Arroyo and colleagues (2012), who show in vitro that the activation of VChIs causes a barrage of inhibitory postsynaptic currents (IPSCs) in neighboring Pyrs in the sensorimotor cortex [46]. Two recent studies [9,10] used optogenetics and electrophysiology in vitro to study the local output connectivity pattern of cortical VChIs. Interestingly, both studies demonstrated a release of ACh from VChI output synapses.…”
Section: Input-output Properties Of Vchissupporting
confidence: 90%
See 3 more Smart Citations
“…Our results correspond with Arroyo and colleagues (2012), who show in vitro that the activation of VChIs causes a barrage of inhibitory postsynaptic currents (IPSCs) in neighboring Pyrs in the sensorimotor cortex [46]. Two recent studies [9,10] used optogenetics and electrophysiology in vitro to study the local output connectivity pattern of cortical VChIs. Interestingly, both studies demonstrated a release of ACh from VChI output synapses.…”
Section: Input-output Properties Of Vchissupporting
confidence: 90%
“…The estimates regarding the sparseness of VChIs vary between studies [7,9,11,47]. In order to obtain an independent estimate of the number and the spatial distribution of VChIs, we used immunostaining in wild-type (WT) mice (Fig 1A and 1B; see Materials and methods).…”
Section: Cortical Vchis: Density and Proportionmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphology and distribution of VChI neurons were recently described and categorized based on two distinct morphological sub-populations, bipolar/bi-tufted and multipolar 25,34,35 .…”
Section: Morphological Classification Of Vchismentioning
confidence: 99%